Review on operation control of cold thermal energy storage in cooling systems - Huan Wang; Baoshan Xie; Chuanchang Li (Energy and Built Environment)
Cold storage technology is useful to alleviate the mismatch between the cold energy demand and supply. The integration of cold energy storage in cooling system is an effective approach to improve the system reliability and performance. This review provides an overview and recent advances of the cold thermal energy storage (CTES) in refrigeration cooling systems and discusses the operation control for system optimization. Firstly, the composition and principles of cooling systems coupled with CTES are presented. Special attention was paid to cold storage medium of phase change material (PCM) with high energy density and stable phase change temperature. Then, based on the classification of driven energy, the different applications of passive or active cooling systems with CTES are classified, including building cooling, cold chain logistics, and other refrigeration systems. Most importantly, the operation control which is necessary to performance optimization is presented, including operational control strategies, cold load predictions, and economic evaluation methods. Three types of operational control strategies are summarised using water storage and cooling system as an example. Two types of cold load predictions, parametric regression and artificial neural network method, are introduced. Three aspects of economic costs are summarized in terms of initial equipment investment cost, operational cost, and life-cycle cost are summarized. Finally, an outlook on the development of cooling systems using CTES is given.